1999
DOI: 10.1002/(sici)1521-4141(199902)29:02<571::aid-immu571>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal Langerhans cells lack functional mannose receptors and a fully developed endosomal/lysosomal compartment for loading of HLA class II molecules

Abstract: Langerhans cells (LC) represent the dendritic cell (DC) lineage in the epidermis. They capture and process antigens in the skin and subsequently migrate to the draining lymph nodes to activate naive T cells. Efficient uptake and processing of protein antigens by LC would, therefore, seem a prerequisite. We have now compared the capacity of human epidermal LC, blood-derived DC and peripheral blood mononuclear cells to endocytose and present (mannosylated) antigens to antigen-specific T cells. Moreover, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…Interest-ingly, Langerin possesses a single carbohydrate recognition domain with a glutamate-proline-asparagine motif predicting mannose type specificity (Valladeau et al, 2000), a potentially important property because LCs lack classical mannose receptors (Mommaas et al, 1999). Ligands of Langerin have yet to be described, however, it could serve as a receptor for the capture of specific microbial antigens by this unique population of antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interest-ingly, Langerin possesses a single carbohydrate recognition domain with a glutamate-proline-asparagine motif predicting mannose type specificity (Valladeau et al, 2000), a potentially important property because LCs lack classical mannose receptors (Mommaas et al, 1999). Ligands of Langerin have yet to be described, however, it could serve as a receptor for the capture of specific microbial antigens by this unique population of antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…As is typical of highly secretory cells, the nuclei of LS-DCs are located to one side of the cell. The cytoplasms are filled with both multivesicular and multilaminar structures that appear to be intracellular endosomal/lysosomal MHC class II-positive compartments, which likely play a role in antigen processing and the formation of peptide-MHC II complexes [22][23][24][25][26][27][28][29][30][31][32]. Multivesicular structures have been demonstrated to be a prerequisite for the formation of multilaminar structures, since endocytosed antigens are first Bykovskaia, Shurin, Graner et al observed in multivesicular compartments, and then subsequently, can be localized in multilaminar structures [25].…”
Section: Discussionmentioning
confidence: 99%
“…Multivesicular structures have been demonstrated to be a prerequisite for the formation of multilaminar structures, since endocytosed antigens are first Bykovskaia, Shurin, Graner et al observed in multivesicular compartments, and then subsequently, can be localized in multilaminar structures [25]. Multi-laminar structures, such as MIICs, are intracellular compartments that represent the most abundant storehouse of intracellular MHC class II molecules [22] and are detected in such diverse APCs as human B lymphoblastoid cells [23], DCs, Langerhans cells, and macrophages [25][26][27][28]. MIIC structures are designed to process antigenic peptides derived from extracellular sources and to then load them into MHC class II molecular complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Among DC populations, MR expression is abundant on mouse bone marrow-derived DC, human monocyte-derived DCs and interstitial DCs, such as dermal DCs (Sallusto et al, 1995;Uccini et al, 1997). MR is not expressed by Langerhans cells in the epidermis or by plasmacytoid DCs (Mommaas et al, 1999;Guo et al, 2000). Interestingly, MR-expressing DCs are found in the epidermis of patients with active dermatitis, suggesting that these MR-expressing APCs may be mobilized to inflammatory sites (Wollenberg et al, 2002), or MR expression may be induced locally by inflammatory mediators.…”
Section: Targeting Antigens To Clrsmentioning
confidence: 99%